2013
DOI: 10.1002/jcp.24460
|View full text |Cite
|
Sign up to set email alerts
|

Wnt16 is Involved in Intramembranous Ossification and Suppresses Osteoblast Differentiation Through the Wnt/β‐Catenin Pathway

Abstract: In the course of embryonic development skeletal elements form either through intramembranous or endochondral ossification. Wnt proteins play diverse roles during vertebrate skeletal development. Wnt16 is a key factor in developing long bones, but its exact role in craniofacial bone formation remains unclear. This study was initially undertaken to investigate the expression of Wnt16 during craniofacial bone development in mouse embryos. Wnt16 expression in the osteoid of calvaria, maxilla, and mandible started … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 49 publications
3
37
0
Order By: Relevance
“…(5153) Wnt16 is expressed in osteoid tissue of craniofacial bones during embryonic development in mice, and suppresses osteoblast differentiation through the canonical β-catenin pathway in MC3T3-E1 preosteoblasts. (54) Several GWA meta-analysis studies have demonstrated that WNT16 intron 3 SNP rs3801387, (41) exon 2 rs2908004 (WNT16B G82R) and exon 4 rs2707466 (WNT16B T263I) (55,56) as well as intergenic SNP rs10242100 (31) are associated with BMD phenotypes (Figure 3). However, functional roles of non-coding SNPs rs10242100 and rs3801387, which are in almost perfect LD [ r 2 = 0.915 in 1KG Pilot 1 CEU Population by applying SNAP tool (46) ], remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…(5153) Wnt16 is expressed in osteoid tissue of craniofacial bones during embryonic development in mice, and suppresses osteoblast differentiation through the canonical β-catenin pathway in MC3T3-E1 preosteoblasts. (54) Several GWA meta-analysis studies have demonstrated that WNT16 intron 3 SNP rs3801387, (41) exon 2 rs2908004 (WNT16B G82R) and exon 4 rs2707466 (WNT16B T263I) (55,56) as well as intergenic SNP rs10242100 (31) are associated with BMD phenotypes (Figure 3). However, functional roles of non-coding SNPs rs10242100 and rs3801387, which are in almost perfect LD [ r 2 = 0.915 in 1KG Pilot 1 CEU Population by applying SNAP tool (46) ], remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to bone, we and others have recently shown that in osteoblasts Wnt16 signals via the canonical WNTcascade. 40,41 However, in contrast with the emergent hypothesis that Wnt16 has a positive effect on bone (similar to activation of canonical WNT signaling) and with the findings that Wnt16 deletion leads to decreased WNT signaling in cortical bone, Hendrickx et al 34 have reported that one of the WNT16 single-nucleotide polymorphisms, which falls in the Kozak sequence of WNT16 and is associated with increased WNT16 translation and increased BMD, does not activate b-catenin-dependent signaling. This suggests that either Wnt16 is a weak canonical WNT ligand in osteoblasts and/or that its ability to activate the canonical cascade may be dependent on multiple stochastic changes in the levels of biological factors in the microenvironment and on the presence and/or variations in the levels of specific receptors, antagonists and agonists.…”
Section: Wnt16 and The Regulation Of Bone Homeostasismentioning
confidence: 98%
“…40 Recently, our studies have shed light on the role of Wnt16 in postnatal bone homeostasis in mice and in the mechanism(s) by which this WNT ligand affects bone biology. 40,41 The first study demonstrating that Wnt16 contributes to cortical bone mass in mice was part of the Lexicon's Genome5000 program focused to characterize mouse knockout phenotypes of genes with pharmaceutical potential. These initial findings were included in two BMD GWAS, in which A new WNT on the bone F Gori et al the WNT16 gene was found to be strongly associated with cortical bone thickness and fracture susceptibility in humans.…”
Section: Wnt16 and The Regulation Of Bone Homeostasismentioning
confidence: 99%
“…The Notch signaling pathway has also been linked to craniosynostosis as a result of its association with tissue boundary formation, which is important during the patterned growth of the skull (Yen et al, 2010). Additionally, a microarray study has identified upregulation of Wnt signaling in tissues (Miraoui et al, 2010), and other studies have identified WNT5B expression in postnatal growth plates (Andrade et al, 2007) and WNT16 as suppressing osteoblast differentiation in craniofacial bone formation (Jiang et al, 2014). Here, we used correlation analysis to investigate whether these transcripts are associated with SSC.…”
Section: −4mentioning
confidence: 99%